(untitled) (International journal of medical sciences, 2026)
Sluder’s syndrome, a rare neuralgia of the pterygopalatine ganglion, causes unilateral facial pain with autonomic symptoms (rhinorrhea, lacrimation). Misdiagnosis is common due to overlapping features with migraine, cluster headache, and dental pathologies. This article analyzes clinical characteristics, pathophysiological mechanisms (neurogenic inflammation, central sensitization), and the impact of comorbidities (rhinosinusitis, autoimmune disorders). Modern treatments, including ganglion blocks, radiofrequency ablation, and neurostimulation, are discussed. Early diagnosis is emphasized to prevent pain chronification. The review integrates recent studies (2022–2024) and highlights interdisciplinary management strategies.